Preliminary results on the High-Resolution Seismic Survey at Puerto Foster Bay, Deception Island, Antarctica - Ayres Neto, Arthur; Magrani, Fabio Jose Guedes; Dias, Rodolfo Jasao [UNESP]; Salaroli, Alexandre [UNESP]; Dauern, Ana Lucia; Louza, Fabio (Ieee, 2013)
A high-resolution seismic survey was conducted within Puerto Forster Bay, Deception Island, Antarctica, in order to study the seafloor geological characteristics. This bay was originally the volcano's crater and became a bay after part of the wall was destroyed allowing the sea water to come in. There are areas of long term geothermal activity and it is classified as a restless caldera with a significant volcanic risk. The results showed the presence of four different seismic echo-characters. The first one is defined by a series of sub-bottom reflectors parallel to the seafloor indicating the deposition under low energy environment. The other two are characterized by a chaotic / transparent sub-bottom layer, maybe associated to deposits of volcanic material or slided debris from the flanks of the volcano. Moreover, these echo-characters are associated to more irregular seafloor morphology. No evidences of gassy sediments, faults or fluid migration in the seafloor were observed on the seismic records indicating that recent volcanic activity observed in the period between 1967 and 1970 is happening in another point of the volcano separated from the old crater. © 2013 IEEE.
Keywords: Antarctica; Deception Island; High-resolution seismic; Marine geology